Use of cannabis and risk of advanced liver fibrosis in patients with chronic hepatitis C virus infection: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
© 2018 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd Objectives: Chronic hepatitis C virus (HCV) infection is one of the most common chronic liver diseases. Several risk factors for the progression of liver fibrosis among these patients have been identified. Use of cannabis could be another risk factor, but the results from epidemiological studies remain inconclusive. Methods: Comprehensive literature review was conducted using MEDLINE and EMBASE databases through December 2017 to identify studies that compared the risk of advanced liver fibrosis among HCV-infected patients who use and who do not use cannabis. Effect estimates from each study were extracted and combined together using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: A total of three cohort studies with 898 participants met the eligibility criteria and were included in the meta-analysis. The risk of advanced liver fibrosis among HCV-infected patients who use cannabis was numerically higher than those who do not use cannabis, although the result did not achieve statistical significance (pooled odds ratio, 1.77; 95% confidence interval, 0.78–4.02). The statistical heterogeneity was high with an I2 of 75%. Conclusions: This meta-analysis showed that the risk of advanced liver fibrosis among HCV-infected patients who use cannabis was higher than those who do not use cannabis, but the result was not statistically significant. Further studies are required to better characterize the risk.